Does reduced usage of antibiotics in livestock production mitigate the spread of antibiotic resistance in soil, earthworm guts, and the phyllosphere?. (March 2020) - Zhou, Shu-yi-dan; Zhu, Dong; Giles, Madeline; Daniell, Tim; Neilson, Roy; Yang, Xiao-ru
Graphical abstract: Highlights: Manure application impacted the resistome in soil, earthworms and phyllosphere. Manure with reduced antibiotic burden reduced the spread of the antibiotic resistome. Shared ARGs and OTUs were founded within soil-earthworm-phyllosphere system. Abstract: The overuse of antibiotics in animal husbandry is widespread and believed to significantly contribute to the selection of antibiotic resistance genes (ARGs) in animals. Thus, there is a global drive to reduce antibiotic use in the agricultural sector. However, it has not been established whether a reduction in the use of antibiotics in livestock production would be effective in reducing the spread of ARGs. A microcosm approach was used to determine how the addition of manure with either reduced antibiotic levels or with typical antibiotic levels could affect the spread of antibiotic resistance genes between soil, earthworms and the phyllosphere. When compared to the control soil, earthworm and phyllosphere samples had the greater increase in ARG abundance in conventional manure treatments ( P  < 0.05). Reduced antibiotic manure also enriched the abundance of ARGs in the phyllosphere and soil but not earthworm guts when compared to the control ( P  < 0.05). In both soil and earthworm guts, the enrichment of ARGs was lower in reduced antibiotic manure than in conventional manure. This study has identified bacterial transfer through the soil-earthworm-phyllosphere system as a potential means to spread ARGs between habitats after fertilization with livestock derived manures.